Psycho-emotional and cognitive background in children with juvenile rheumatoid arthritis (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
One of the neurological complications in patients with juvenile rheumatoid arthritis is a disturbance of psycho-emotional background and cognitive disorders. Due to the lack of a pronounced clinical picture and insufficient awareness in the literature, the topic is topical.